Identify the second step to solving this equation for x.

-3(x+6)=21

1 answer

The second step to solving this equation for x is to divide both sides of the equation by -3.

This yields:
$$\frac{-3(x+6)}{-3} = \frac{21}{-3}$$

Simplifying both sides gives:
$$x+6 = -7$$
Similar Questions
  1. Solving the equation 6x + 2(x − 1) = 30Given: 6x + 2(x − 1) = 30 Step 1: 6x + 2x − 2 = 30 Step 2: 8x − 2 = 30 Step 3: 8x
    1. answers icon 3 answers
  2. Solving the equation 6x + 2(x − 1) = 30Given: 6x + 2(x − 1) = 30 Step 1: 6x + 2x − 2 = 30 Step 2: 8x − 2 = 30 Step 3: 8x
    1. answers icon 1 answer
    1. answers icon 3 answers
    1. answers icon 1 answer
more similar questions